Uji Potensi Karbon Aktif Berbahan Kulit Durian Sebagai Media Immobilisasi Asam Lemak Hidroksamat - Muhsinun Muhsinun; Syamsul Hidayat; Emsal Yanuar (Lembaga Publikasi Ilmiah Nusantara, 2025)
The utilization of biomass waste as a raw material for functional materials represents a sustainable approach in the development of carbon-based materials. This study aims to evaluate the potential of activated carbon derived from durian peel as a support for the immobilization of fatty hydroxamic acids. Activated carbon was synthesized through sequential stages of raw material preparation, carbonization, and chemical activation to produce a porous material with surface properties favorable for immobilization processes. The characterization results indicate the formation of a well-developed porous structure along with the presence of oxygen-containing functional groups, which play a crucial role in interactions with fatty hydroxamic acids. Fatty hydroxamic acids were synthesized from vegetable oil and employed as the target compounds in the immobilization process. Immobilization was carried out using a direct contact method between the activated carbon and the fatty hydroxamic acid solution under controlled conditions. The results demonstrate that durian peel–based activated carbon effectively immobilizes fatty hydroxamic acids through a combination of physical adsorption mechanisms and chemical interactions on the carbon surface. The immobilization efficiency obtained indicates that pore characteristics and surface functional groups of the activated carbon strongly influence its performance as an immobilization medium. Stability tests further reveal that the immobilized system exhibits satisfactory resistance to washing and repeated use. Overall, this study confirms that activated carbon derived from durian peel has significant potential as an immobilization medium for chemical compounds, while simultaneously adding value to biomass waste and supporting the development of environmentally friendly materials for chemical and environmental applications.